2004
DOI: 10.1029/2004je002254
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric rotational effects on Mars based on the NASA Ames general circulation model: Angular momentum approach

Abstract: [1] The NASA Ames general circulation model has been used to compute time series for atmospheric products of inertia and relative angular momentum terms. Model outputs were used also to compute time series representing the inertia terms due to CO 2 condensation and sublimation on the surface of Mars. Some of these terms were used to generate time series representing the forcing functions for the equatorial components of the linearized Liouville equations of rotational motion. These equations were then solved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The main atmospheric forcing is at seasonal frequencies, resulting in largest wobble amplitudes of about 10 mas at 1, 1/2, and 1/3 year, the exact values depending on the atmospheric and internal structure models used (Chao and Rubincam, 1990;Defraigne et al, 2000;Sanchez et al, 2004;Van den Acker et al, 2002;Yoder and Standish, 1997). The annual and semiannual wobble amplitudes, respectively, 13.6 and 11.2 mas, observationally determined by Konopliv et al (2006) agree remarkably well with the theoretical values of 12.0 and 9.8 mas, respectively, of Van den Acker et al (2002).…”
Section: Seasonal Polar Motionsupporting
confidence: 76%
See 2 more Smart Citations
“…The main atmospheric forcing is at seasonal frequencies, resulting in largest wobble amplitudes of about 10 mas at 1, 1/2, and 1/3 year, the exact values depending on the atmospheric and internal structure models used (Chao and Rubincam, 1990;Defraigne et al, 2000;Sanchez et al, 2004;Van den Acker et al, 2002;Yoder and Standish, 1997). The annual and semiannual wobble amplitudes, respectively, 13.6 and 11.2 mas, observationally determined by Konopliv et al (2006) agree remarkably well with the theoretical values of 12.0 and 9.8 mas, respectively, of Van den Acker et al (2002).…”
Section: Seasonal Polar Motionsupporting
confidence: 76%
“…The annual and semiannual wobble amplitudes, respectively, 13.6 and 11.2 mas, observationally determined by Konopliv et al (2006) agree remarkably well with the theoretical values of 12.0 and 9.8 mas, respectively, of Van den Acker et al (2002). The fact that the amplitude at 1/3 year is expected to be of the same order of magnitude as the amplitudes at 1 and 1/2 year is most likely due to the resonance with the Chandler wobble with a period of about 200 days (eqn [47], Dehant et al, 2003;Konopliv et al, 2006;Sanchez et al, 2004;Van Hoolst et al, 2000b;Yoder and Standish, 1997;Zharkov and Gudkova, 2005).…”
Section: Seasonal Polar Motionsupporting
confidence: 72%
See 1 more Smart Citation
“…The main atmospheric forcing is at seasonal frequencies, resulting in largest wobble amplitudes of about 10 mas at 1, 1/2, and 1/3 year, the exact values depending on the atmospheric and internal structure models used (Chao and Rubincam, 1990;Yoder and Standish, 1997;Defraigne et al, 2000;Van den Acker et al, 2002;Sanchez et al, 2004). The large amplitude at 1/3 year is most likely due to the resonance with the Chandler wobble with a period of about 200 days (eqn [46], Yoder and Standish, 1997;Van Hoolst et al, 2000b;Dehant et al, 2003;Zharkov and Gudkova, 2005;Konopliv et al, 2006).…”
Section: Seasonal Polar Motionmentioning
confidence: 99%
“…The contribution of the atmospheric pressure is about twice that of the contribution of the ice caps. This effect is proportional to the Love number k 2 , for which Sanchez et al (2004) used the value determined by Yoder et al (2003), who showed that this value is a strong indication that the core is, at least partially, liquid. The NASA Ames GCM has been used by Sanchez et al (2004) to estimate polar motion series.…”
Section: Seasonal Polar Motionmentioning
confidence: 99%